Integrated modeling for flood hazard mapping using watershed modeling system - Sadrolashrafi, Seyedeh Sara; Mohamed, Thamer Ahmed; Mahmud, Ahmad Rodzi; Kholgi, Majid Khayyat; Samadi, Amir (Science Publications, 2008)
In this stduy, a new framework which integrates the Geographic Information System (GIS) with the Watershed Modeling System (WMS) for flood modeling is developed. It also interconnects the terrain models and the GIS software, with commercial standard hydrological and hydraulic models, including HEC-1, HEC-RAS, etc. The Dez River Basin (about 16213 km2) in Khuzestan province, IRAN, is domain of study because of occuring frequent severe flash flooding. As a case of study, a major flood in autumn of 2001 is chosen to examine the modeling framework. The model consists of a rainfall-runoff model (HEC-1) that converts excess precipitation to overland flow and channel runoff and a hydraulic model (HEC-RAS) that simulates steady state flow through the river channel network based on the HEC-1, peak hydrographs. In addition, it delineates the maps of potential flood zonation for the Dez River Basin. These are achieved based on the state of the art GIS with using WMS software. Watershed parameters are calibrated manually to perform a good simulation of discharge at three sub-basins. With the calibrated discharge, WMS is capable of producing flood hazard map. The modeling framework presented in this study demonstrates the accuracy and usefulness of the WMS software for flash flooding control. The results of this research will benefit future modeling efforts by providing validate hydrological software to forecast flooding on a regional scale. This model designed for the Dez River Basin, while this regional scale model may be used as a prototype for model applications in other areas.